Pengaruh Umur, Pendidikan, Pekerjaan Terhadap Pendapatan Rumah Tangga Miskin di Desa Bebandem - Dwiandana Putri, Arya; Setiawina, Djinar (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2013)
Poverty continues to be a phenomenal problem throughout Indonesia history, as well as the circumstances in Bebandem village, Karangasem Bali. With regard to the conditions that have been occured in that village, this study aims to: (1) To find out the effect of age, education and type of work simultaneously on the income of poor households in the Bebandem village, Karangasem, (2) To find out the effect of age, education, and type of work partially on the income of poor households in the Bebandem village, Karangasem, and (3) To find out the dominant effect among age, education and type of work on the income of poor households in the Bebandem village, Karangasem. By using number of population were 95 respondents with data analysis techniques of multiple linear regression. The results shows that: (1) In simultaneous the factors of age, education and type of work, have significant effect on the income of poor households in the Bebandem village, Karangasem. (2) In Partial the variable of age, education and type of work have positive and significant effect on the income of poor households in the Bebandem village, Karangasem. Age variable have negative affect on the incomes of poor households in the Bebandem village, Karangasem. (3) the dominant factor have affect on the income of poor households in the Bebandem village, Karangasem is age variable.
Keywords: Age; education; type of job; poor households